POSTDIAGENETIC ALTERATIONS OF CLAYEY ROCKS AT RELATIVELY HIGH TEMPERATURES IN THE LIASSIC SEQUENCE OF THE CENTRAL CAUCASUS - Gavrilov Y.O.; Tsipurskiy S.I. (My University, 1988)
The aim of our work was to estimate the effect of the temperature factor on clayey rocks and ascertain the resulting alteration of their mineral composition. We studied Lower Jurassic sections located comparatively near one another (9 to 10 km) in the left band of the Baksan River, central Caucasus, but the rocks were transformed to a different extent by postdiagenetic alteration, chiefly by thermal reworking. The degree of heating of the rocks at different places where they are exposed evidently was not equal, as reflected in the details of their alteration. Moreover, as can be seen from the above data, the original composition of clayey deposits, formed during sedimentation and the initial stages of lithogenesis, was very important in the subsequent process that produced the secondary mineral associations in rocks, particularly where the latter were heated.
Keywords: Jurassic; Mesozoic::Jurassic; Мезозой::Юрская